Histological and biophysical changes of cassava roots during retting, a key step of fufu processing - Wakem, G.A.; Tonfack, L.B.; Youmbi, E.; Fotso-Kaute, A.; Masso, C.; Fiaboe, K.; Ndango, R.; Tize, I.; Grabulos, J.; Dufour, D.; Ndjouenken, R.; Mbeguie-A-Mbeguie, D. (Wiley, 2024)
BACKGROUND Retting is a key step of cassava processing into widely consumed foods (fufu, chikwangue, miondo and bobolo) in sub-Saharan Africa. For some populations, retting ability is a major quality criterion that drives the adoption of new cassava varieties. Despite this importance, the physiological basis associated with this process remains poorly understood, and should lead to improved screening tools for breeding. Eight cassava varieties contrasting in retting ability properties were used in the present study. Roots and soaking water were sampled during retting and characterized at both histological and biochemical levels.